Réponses

2014-09-06T20:11:46+02:00
r = 7/3, s = - 5 et t = - 3/7
Calculer les expressions suivantes :

a) r + s - t
7/3 + (- 5) - (- 3/7)
= 7/3 - 5 + 3/7
= 7 x 7 / 3 x 7 - 5 x 21 / 1 x 21 + 3 x 3 / 7 x 3
= 49/21 - 105/21 + 9/21
= - 47/21


b) r x s : t
7/3 x (- 5) : - 3/7
= - 35/3 :  - 3/7
= - 35/3 x - 7/3
= 245/9

c) r - s : t
7/3 - (- 5) : - 3/7
= 7/3 + 5 : - 3/7
= 7/3 + 5 x - 7/3
= 7/3 - 35/3
= - 28/3

d) r : t - s

7/3 : - 3/7 - (- 5)
= 7/3 : - 3/7 + 5
= 7/3 x - 7/3 + 5
= - 49/9 + 5 x 9 /1 x 9
= - 49/9 + 45/9
= - 4/9